Proteolysis-targeting chimeras as a novel strategy for targeting epigenetic mechanisms in Plasmodium falciparum parasites - Birkholtz, Lyn-Marie (University of Pretoria, 2025)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2024.